2007
DOI: 10.1248/bpb.30.2018
|View full text |Cite
|
Sign up to set email alerts
|

Toxic Effects of TCDD on Osteogenesis through Altering IGFBP-6 Gene Expression in Osteoblasts

Abstract: Since 2,3,7,8-tetrachlorodibenzo-p-dioxin (TCDD) has reproductive and developmental toxicity as an estrogen antagonist, we investigated the effects of TCDD on osteogenesis in rat skeleton and the human female-responsive osteoblastic osteosarcoma cell line SaOS-2. Rat fetuses were exposed to 5, 10, or 15 m mg/kg TCDD on gestation day (GD) 10. TCDD dose-dependently induced single or multiple rat fetal skeletal development malformations in vivo. In vitro, 10 nM TCDD significantly inhibited cell proliferation in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 73 publications
0
11
0
Order By: Relevance
“…However, the molecular mechanism of estrogen signaling through ER in IGFBP-6 transcription has not been determined. In order to understand the mechanisms of estrogen in IGF signaling, we previously investigated estrogen regulation of IGFBP-6 gene in vivo (Guo et al, 2003(Guo et al, , 2007. Herein, we present evidence that the human osteoblastic-like cell line SaOS-2 expresses IGFBP-6 and that estrogen increases the abundance of both IGFBP-6 mRNA and protein in the presence of ER.…”
Section: Figurementioning
confidence: 78%
See 4 more Smart Citations
“…However, the molecular mechanism of estrogen signaling through ER in IGFBP-6 transcription has not been determined. In order to understand the mechanisms of estrogen in IGF signaling, we previously investigated estrogen regulation of IGFBP-6 gene in vivo (Guo et al, 2003(Guo et al, , 2007. Herein, we present evidence that the human osteoblastic-like cell line SaOS-2 expresses IGFBP-6 and that estrogen increases the abundance of both IGFBP-6 mRNA and protein in the presence of ER.…”
Section: Figurementioning
confidence: 78%
“…Transfection with either ERα or ERβ causes U2OS cell sensitivity to E2 (Lima et al, 2004;Kallio et al, 2008). We previously reported that E2 (1 μM) does not positively regulate cell proliferation in MC-3T3-E1 cells (Guo et al, 2007). However, herein, SaOS-2 cells were transfected with the wild-type human ERα expression vector and E2 up-regulated cell proliferation 2 fold in SaOS-2 cells, but in dose independent manner within the range of concentration of 0.01 to 1 μM.…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations